Techno-Economic Analysis Of Establishing A Seaweed Processing Plant With A Flexible Manufacturing System - Edi Djatmika; Hermawan Thaheer; Legis Tsaniyah; Ra’iyatu Imadidin (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Seaweed is a mainstay in the development of the blue economy in Indonesia, with production reaching 8.6 million tons in 2022. In Indonesia, the types of seaweed cultivated are Euchema sp. as a source of carrageenan and Gracilaria sp. which is a type of seaweed often cultivated in ponds as a source of agar. The two types of seaweed have different characteristics, so they have different extraction methods in the processing. Separate process designs for the two types of seaweed are inefficient due to different harvesting patterns. Several processing machines for the two types of seaweed function similarly, so they can be rotated in the processing. With some additional equipment, a Flexible Manufacturing System (FMS) is produced, in which the factory system can process agar-agar and kataginan alternately. This study was conducted to analyze the feasibility of a seaweed factory designed with the FMS model. The analysis was carried out using a financial feasibility method with the Weighted Average Cost of Capital (WACC) as a reference indicator. The Capex for the FMS factory with a combined product capacity of 1500 tons/year is estimated at Rp. 60.6 billion with Opex of Rp. 8.65 billion. The factory is projected to generate an average net profit of 9.77%. The investment itself will be recovered between the 7th and 8th year. The establishment and operation of the FNS seaweed factory is deemed feasible with a positive NPV of IDR 28.88 billion, an IRR of 17.81% higher than the WACC of 10.49%, and a PI of 1.42. The break-even point for the factory is reached at a production rate of 667.38 tons per year, or approximately 44.49% of installed capacity. This condition allows the factory to adjust to seaweed harvest patterns to overcome raw material shortages.